2008
DOI: 10.1111/j.1537-2995.2008.01670.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of hemolysis and red cell mechanical fragility in blood collected with different cell salvage suction devices

Abstract: Although the variable-pressure device produced a significant reduction in hemolysis during one-pass blood collection, the clinical significance of this reduction is not clear. In relative terms, the variable-pressure device would recover an extra 10 mL of RBCs for every liter of salvaged RBCs, which is negligible compared to the blood loss in major surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 18 publications
2
30
0
Order By: Relevance
“…This seems not to be the case if blood is suctioned from containers (Waters et al, 2007). If suctioned from a flat surface the vacuum pressure does make a difference though it is very small (Yazer et al, 2008). 'Although the variable-pressure device produced a significant reduction in hemolysis during one-pass blood collection, the clinical significance of this reduction is not clear.…”
Section: Vacuum Type and Pressurementioning
confidence: 84%
See 1 more Smart Citation
“…This seems not to be the case if blood is suctioned from containers (Waters et al, 2007). If suctioned from a flat surface the vacuum pressure does make a difference though it is very small (Yazer et al, 2008). 'Although the variable-pressure device produced a significant reduction in hemolysis during one-pass blood collection, the clinical significance of this reduction is not clear.…”
Section: Vacuum Type and Pressurementioning
confidence: 84%
“…In another study Yazer et al also conclude that a higher level of airblood contact increases the level of hemolysis. They also found that hemolysis was decreased by using a vacuum suction device with variable pressure (Yazer et al, 2008).…”
Section: Washed Autologous Transfusionmentioning
confidence: 99%
“…Hemolysis during cardiac surgery has previously been reported and is considered to be caused by cardiopulmonary bypass circuits, transfusion of stored red blood cells, and cell salvage devices. 8,[19][20][21] Interestingly, we found that the total release of plasma fHb was independently correlated with urine NAG, which in turn was independently associated with the postoperative increase in serum creatinine. This clinical observation is supported by rodent experiments in which intravenous infusion of fHb increased urine NAG concentrations 10-fold, while decreasing GFR by 30%.…”
Section: Discussionmentioning
confidence: 98%
“…For assessment of MF, we used the procedure described by Kameneva's group [33,34,35] with slight changes. 3 ml of RBC suspension (control, stored, and stored-rejuvenated) were rocked in glass test tubes (13 × 100 mm, Fisher Scientific), containing 5 steel beads (1/8-inch stainless-steel beads, Nationskander California Corp., Anaheim, CA, USA).…”
Section: Methodsmentioning
confidence: 99%